Invariant Natural Killer T Cell Deficiency and Functional Impairment in Sleep Apnea: Links to Cancer Comorbidity - Gaoatswe, Gadintshware (Sleep, 2015)
STUDY OBJECTIVES: Emerging evidence links obstructive sleep apnea (OSA) with increased cancer incidence and mortality. Invariant natural killer T (iNKT) cells play an important role in cancer immunity. We hypothesized that patients with OSA have low number of circulating invariant natural killer T (iNKT) cells, which may also be functionally impaired. This study aims to evaluate the frequency of circulating iNKT cells in OSA. DESIGN: We evaluated the frequency of circulating iNKT cells by flow cytometry in 33 snorers being assessed for possible OSA. Using iNKT cell lines, we also evaluated the effect of exposure to hypoxia over 24 hours on apoptosis, cytotoxicity, and cytokine production. SETTING: Teaching hospital based sleep unit and research laboratory. PATIENTS: Thirty-three snorers were evaluated: 9 with no OSA (apnea-hypopnea frequency [AHI] < 5/h), 12 with mild-moderate OSA (AHI 5–30) and 12 with severe OSA (AHI > 30). MEASUREMENTS AND RESULTS: Patients with severe OSA had considerably fewer iNKT cells (0.18%) compared to patients with mild-moderate (0.24%) or no OSA (0.35%), P = 0.0026. The frequency of iNKT cells correlated negatively with apnea-hypopnea index (r = −0.58, P = 0.001), oxygen desaturation index (r = −0.58, P = 0.0003), and SpO(2)% < 90% (r = −0.5407, P = 0.005). The frequency of iNKT cells increased following 12 months of nCPAP therapy (P = 0.015). Hypoxia resulted in increased apoptosis (P = 0.016) and impaired cytotoxicity (P = 0.035). CONCLUSION: Patients with obstructive sleep apnea (OSA) have significantly reduced levels of circulating invariant natural killer T (iNKT) cells and hypoxia leads to impaired iNKT cell function. These observations may partly explain the increased cancer risk reported in patients with OSA. CITATION: Gaoatswe G, Kent BD, Corrigan MA, Nolan G, Hogan AE, McNicholas WT, O'Shea D. Invariant natural killer T cell deficiency and functional impairment in sleep apnea: links to cancer comorbidity. SLEEP 2015;38(10):1629–1634.